The Influence of The Digital Economy on The Competitiveness of The Coffee Industry in Binjai: A Sharia Economic Perspective - Oktaviani, Chintia; Waqqosh, Abi (Manunggal Halim Jaya, 2026)
This study aims to find out how the influence of the digital economy on the competitiveness of the coffee industry in the city of Binjai is reviewed through the sharia economy. The method used in this study is quantitative. The population in this study is coffee industry business actors in the city of Binjai who have used the digital economy in carrying out their business activities, which amounted to 79 people. The research sample amounted to 51 people with a sampling technique, namely purposive sampling. Data collection techniques are literature studies and questionnaires, and documentation. The data analysis techniques used were descriptive analysis, validity test, classical assumption test, simple linear regression analysis, and hypothesis test. The results of the study show that the digital economy has a significant effect on the competitiveness of the coffee industry in the city of Binjai, or Ha. This is evidenced by a simple linear regression equation, namely DS = 1.064 + 0.322X + e. The results of the t-test showed a tcal value of 4.248 > a ttable of 1.677 and a significance of 0.000 < 0.05. Then, based on the results of the determination coefficient test, the R-squared value was obtained as 0.721, or 72.1%, while the other 27.9% was influenced by other factors that were not studied in this research. Reviewed according to Sharia economics, most of the coffee industry business actors in the city of Binjai have implemented the business pillars taught in Islam, namely the existence of a party between the seller and the buyer, the existence of a sighah or contract, the subject of the contract, and the purpose of the sales contract do not deviate. The implications of the study show that the digital economy makes business processes more efficient by reducing time and costs. The research also found that the digital economy has a positive impact on the competitiveness of the coffee business.